Factors affecting secure software development practices among developers- an investigation - Ahmed Maher, Zulfikar; Shaikh, Humaiz; Khan, Mohammad Shadab; Arbaaeen, Ammar; Shah, Asadullah (Institute of Electrical and Electronics Engineers Inc., 2019)
An evidently dominate problem in the software development domain is that software security is not consistently addressed from the initial phase of software development which escalates security concerns, results in insecure software development. Several secure software development methodologies were introduced in literature and recommended to the industry but they are usually ignored by the developers and software practitioners. In this research paper, an extensive literature review is performed to find out factors influencing implementations of secure software development practices in industry. Secondly, based on Unified Theory of Acceptance and Use of Technology model 2 (UTAUT2) this study proposes a model to investigate the factors influencing adoption of secure software development practices among software developers.